Extending the human pressures-species response system in the MSP challenge ecosystem simulation platform - Nascimento, Marcela C.; Gonçalves, Magali P.; Lieser, Jasmin; Mayer, Igor; Scotti, Marco (Frontiers in Marine Science, 2025)
The MSP Challenge Simulation Platform assists planners and stakeholders in understanding and managing the complexity of Maritime Spatial Planning (MSP). It allows users to view various data layers covering an entire sea region, assess the status of the socio-ecological system, and create future scenarios for marine space usage over several decades. The platform integrates the ecosystem modelling approach Ecopath with Ecosim (EwE) to support the implementation of evidence-based and ecosystem-based MSP principles from the EU Directive 2014/89/EU. Each regional edition of the MSP Challenge includes a tailored ecosystem model of the basin. The ecosystem model simulates the effects of pressures from human activities by applying functional responses to each trophic group. This article explains how the modelling of pressures and functional responses was extended from the original system, using the western Baltic Sea as an example. It focuses on pressures characteristic of offshore wind farms, an infrastructure increasingly important for achieving European carbon neutrality and reducing reliance on fossil fuels amid energy crises. First, the general noise pressure that included all kinds of noise and vibrations was split into impulsive noise, continuous noise and bottom vibrations, with air disturbance added as a separate component. Second, a new semi-quantitative metric inspired by the Leopold matrix used in Environmental Impact Assessment was applied to link each pressure to the trophic group’s response, making the process more objective. These improvements standardize the functional response inputs and provide detailed insights into the impacts of different human activities on specific trophic groups. The novelties presented here improve the MSP Challenge Platform’s ability to deliver realistic predictions on ecosystem functioning in response to the construction, operation and decommissioning of offshore wind farms, and may foster more robust decision-making for sustainable maritime spatial planning.